A Rare Case of Linear Phlebolith: Foreign Body Discovered in the Femoral Vein - Tariq Alanezi; Abdulmajeed Altoijry; Kaisor Iqbal; Saeed Alabduljabbar; Mohammed Yousef Aldossary; Sultan AlSheikh (Case Reports in Surgery)
Conclusion: This study showcased a rare form of a radiographically visible calcified thrombus in the veins of the lower extremities of our patient. Calcified venous thrombosis in the lower extremities is rare, as previously documented cases of venous calcifications have been observed in the pelvis with round shapes or as phleboliths. The common presentations differ from those in our case, making it important to consider such cases when formulating a differential diagnosis. While the precise mechanisms behind the formation of calcified thrombi remain unclear, this study emphasizes the significance of further exploration and future case studies to shed light on this enigmatic phenomenon.